More work is needed on cost‐utility analyses of robotic‐assisted surgery. Issue 2 (18th June 2022) - Bai, Fei; Li, Meixuan; Han, Jiani; Qin, Yu; Yao, Liang; Yan, Wenlong; Liu, Yujun; He, Gege; Zhou, Yinjuan; Ma, Xiaoya; Aboudou, Taslim; Guan, Ling; et al.
Abstract: Objective: To comprehensively analyze the cost‐utility of robotic surgery in clinical practice and to investigate the reporting and methodological quality of the related evidence. Methods: Data on cost‐utility analyses (CUAs) of robotic surgery were collected in seven electronic databases from the inception to July 2021. The quality of the included studies was assessed using the CHEERs and QHES checklists. A systematic review was performed with the incremental cost‐effectiveness ratio as the outcome of interest. Results: Thirty‐one CUAs of robotic surgery were eligible. Overall, the identified CUAs were fair to high quality, and 63% of the CUAs ranked the cost‐utility of robotic surgery as "favored, " 32% categorized as "reject, " and the remaining 5% ranked as "unclear." Although a high heterogeneity was present in terms of the study design among the included CUAs, most studies (81.25%) consistently found that robotic surgery was more cost‐utility than open surgery for prostatectomy (ICER: $6905.31/QALY to $26240.75/QALY; time horizon: 10 years or lifetime), colectomy (dominated by robotic surgery; time horizon: 1 year), knee arthroplasty (ICER: $1134.22/QALY to $1232.27/QALY; time horizon: lifetime), gastrectomy (dominated by robotic surgery; time horizon: 1 year), spine surgery (ICER: $17707.27/QALY; time horizon: 1 year), and cystectomy (ICER: $3154.46/QALY; time horizon: 3 months). However, inconsistent evidence was found for the cost‐utility of robotic surgery versus laparoscopic surgery and (chemo)radiotherapy. Conclusions: Fair or high‐quality evidence indicated that robotic surgery is more cost‐utility than open surgery, while it remains inconclusive whether robotic surgery is more cost‐utility than laparoscopic surgery and (chemo)radiotherapy. Thus, an additional evaluation is required.